Estrategias de marketing de la Empresa Sociedad Schuldt Vizuete en la ciudad de Babahoyo, de la provincia de Los Ríos periodo 2023. - Muñoz Murillo, Steven Michael (2024)
The case study applied at Sociedad Schultz Vizuete in Babahoyo focuses on analyzing the company's marketing strategies during the period 2023. The methodology employed combines quantitative and qualitative approaches, applying surveys to current customers to collect data on their perception and experience with the company, in addition to conducting an interview with the owner to obtain a deeper insight into the internal strategies and their effectiveness. Among the main results, several problem areas were identified, such as lack of adequate advertising, weak positioning of the brands it markets and low consumer perception of these brands. To optimize these strategies, it is essential to establish clear and measurable objectives, which will help to increase revenues and improve social media presence. The interview revealed a weakness in the digital marketing strategy, indicating that online platforms are not being properly leveraged, which limits the company's reach and visibility. These actions will improve customer loyalty, increase the company's visibility and enable sustained growth in a competitive market.